Analisis Kadar Senyawa Polifenol Dari Teh Daun Tanaman Cacao (Theobroma cacao L.) Secara Spektrofotometri UV-Vis - Desi, Nilma Sri; Maryam, St.; Tahir, Masdiana (Makassar Pharmaceutical Science Journal (MPSJ), 2024)
. Cocoa leaves (Theobroma cacao L.) contain secondary metabolites such as polyphenol compounds, flavanoids, saponins and tannins which are the largest group of phenolic compounds that act as antioxidant compounds. This study aims to determine the levels of polyphenolic compounds produced from cocoa leaf tea preparations (Theobroma cacao L.) based on the comparison of growing places, namely the Wajo, Jeneponto and Malino regions. Quantitative analysis using UV-Vis spectrophotometric method. based on qualitative analysis by Thin Layer Chromatography method using mobile phase n- hexanes: ethyl acetate: methanol with a ratio (2: 7: 2). Based on the results showed that the preparation of cocoa leaf tea (Theobroma cacao L.). As well as quantitative analysis measured at a maximum wavelength of 768 nm with gallic acid comparator standard. Tea samples contain polyphenolic compounds based on the Rf value equivalent to gallic acid comparator of 0.6. based on the analysis of levels from the Wajo area of 16.238 mgGAE/g, Jeneponto area 18.102 mg/GAE/g, and Malino area 6, 752 mgGAE/g and rf value of gallic acid comparator 0.630; rf value of samples from Jeneponto area 0.6; Wajo 0.6 and Malino 0.615. From the above results, it can be concluded that there are polyphenol compounds in tea samples from each region and the largest polyphenol content is found in the Jeneponto area.